Knowledge Exchanges on Integrated Urban Water Management Briefing Note 1—January 2019 (World Bank, Washington, DC, 2019)
This note describes the outcomes of a June 2018 knowledge exchange visit to study urban water management and urban renewal experiences in Brazil. Participants included 23 country representatives and 9 World Bank staff from Ethiopia, Ghana, and Indonesia who visited the two Brazilian cities of São Paulo and Teresina. São Paulo is a mega-city that has addressed serious urban water issues—from water scarcity and flooding to informal settlements and water supply, sanitation, and pollution—over the past couple decades. Teresina, meanwhile, is a medium-sized town that has integrated several sectors in the urban area at project level. Both cities clearly showed how integration beyond traditional borders between sectors and active stakeholder involvement can lead to significant additional benefits for urban inhabitants. Participants learned from these implementation experiences and took home clear guidance and next steps to be incorporated through ongoing World Bank projects.